Bagaimana Peran Moderasi Kepemimpinan dalam Pengujian Kualitas Audit Internal Pemerintah - Muhammad, Kurniawan; Firmansyah, Amrie (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This research empirically tests the influence of internal auditor competence and the internal control system on the quality of government internal audits. This research also tests leadership as a moderating variable. Methodology: Leadership is also examined in this study as a moderating factor. Primary data from questionnaires given to internal auditor at Inspektorat Utama BPK RI. The study sample was composed of the following based on purposive sampling of 43 observations, with data collected through questionnaires, and processed using the Structure Equation Model (SEM) to process the linkert measurement scale. Results: The research results show that internal auditor competency and the internal control system have a positive effect on internal audit quality. This research also concludes that leadership does not strengthen the positive effect of internal auditor competence on the quality of government internal audits nor does it strengthen the positive effect of the internal control system on the quality of government internal audits. Limitations: This study also has limitations in the number of auditor respondents, namely internal auditors who have reviewed the quality of the BPK RI audit. Contribution: This research contributes to the literature on internal audit in public sector organizations which is still rarely examined in Indonesia.